Effects of different technical coordinate system definitions on the three dimensional representation of the glenohumeral joint centre - Campbell, Amity; Alderson, J.; Lloyd, D.; Elliott, B. (Springer, 2009)
This study aimed to find the most appropriate marker location, or combination thereof, for the centre of the humeral head (Wang et al. in J Biomech 31: 899-908, 1998) location representation during humeral motion. Ten male participants underwent three MRI scans in three different humeral postures. Seven technical coordinate systems (TCS) were defined from various combinations of an acromion, distal upper arm and proximal upper arm clusters of markers in a custom Matlab program. The CHH location was transformed between postures and then compared with the original MRI CHH location. The results demonstrated that following the performance of two near 180° humeral elevations, a combined acromion TCS and proximal upper arm TCS produced an average error of 23 ± 9 mm, and 18 ± 4 mm, which was significantly smaller (p < 0.01) than any other TCS. A combination of acromion and proximal upper arm TCSs should therefore be used to reference the CHH location when analysing movements incorporating large ranges of shoulder motion. © International Federation for Medical and Biological Engineering 2009.